Bilingual Perception of Dysarthric Speech. - Tetzloff, Katerina A.; Fletcher, Annalise R.; Lansford, Kaitlin L.; Barrett, Tyson S.; Borrie, Stephanie A. (Journal of Speech, Language & Hearing Research, 2025)
Purpose: Despite the prevalence of bilingualism, research on the understanding of disordered speech has focused almost exclusively on monolingual populations. Hypothesis-driven studies with dysarthric speech have revealed that greater vocabulary knowledge and working memory support understanding in monolingual listeners. However, whether these explanatory models generalize to bilinguals, who differ in both cognitive and linguistic profiles, is unknown. This study examined whether bilingualism affords a perceptual advantage in understanding dysarthric speech, and whether working memory and vocabulary knowledge contribute to that advantage. Method: Ninety-four listeners, categorized as monolinguals, early bilinguals, or late bilinguals, completed a speech perception task where they transcribed phrases produced by speakers with dysarthria. They also completed working memory and vocabulary assessments. Results: Relative to monolingual and late bilinguals, early bilinguals had equivalent working memory scores, lower vocabulary scores, and reduced intelligibility scores when perceiving dysarthric speech. Vocabulary knowledge, but not working memory, predicted intelligibility scores across all groups. A post hoc correlation analysis within the early bilingual group further revealed that an earlier age of exposure to English was associated with higher intelligibility scores, suggesting that age of language exposure plays a critical role in shaping the linguistic systems that support perception of disordered speech. Conclusions: These findings underscore the importance of vocabulary knowledge and language experience, over working memory, in facilitating understanding of disordered speech. They also highlight the need to refine models of disordered speech perception to account for variability across listener populations, in order to more fully capture the relative contributions of cognitive and linguistic mechanisms.